Association between frailty syndrome and sedentary behavior among community-dwelling older adults in the Amazon region: a cross-sectional study - Santos, Izabelle Santos dos; Silva, Caroline de Fátima Ribeiro; Ohara, Daniela Gonçalves; Matos, Areolino Pena; Pinto, Ana Carolina Pereira Nunes; Pegorari, Maycon Sousa (São Paulo Medical Journal, 2021)
BACKGROUND: Existence of an association between sedentary behavior and frailty among older adults has been suggested. However, there is a lack of studies conducted in Brazil, especially in areas of the Amazon region. OBJECTIVE: To analyze the association between frailty syndrome and sedentary behavior among community-dwelling older adults. DESIGN AND SETTING: Cross-sectional study carried out in Macapá, state of Amapá, Brazil. METHODS: Frailty status was assessed using Fried’s frailty phenotype, and sedentary behavior was evaluated using two questions concerning time spent in a seated position, from the International Physical Activity Questionnaire (IPAQ). A multinomial logistic regression model was used to verify the association between frailty syndrome and sedentary behavior. RESULTS: The final study sample was made up of 411 older adults with a mean age of 70.14 ± 7.25 years and an average daily duration of sedentary behavior of 2.86 ± 2.53 hours. The prevalence of non-frailty was 28.7%, prevalence of pre-frailty was 58.4% and prevalence of frailty was 12.9%. The adjusted analysis showed that there were independent associations between sedentary behavior and pre-frailty (odds ratio, OR = 1.18; 95% confidence interval, CI: 1.03-1.34) and between sedentary behavior and frailty (OR = 1.20; 95% CI: 1.02-1.40). CONCLUSION: Frailty and pre-frailty status were associated with sedentary behavior among community-dwelling older adults.